1988
DOI: 10.1111/j.1432-1033.1988.tb14036.x
|View full text |Cite
|
Sign up to set email alerts
|

Proximity between fluorescent probes attached to four essential lysyl residues in phosphoenolpyruvate carboxylase

Abstract: Phosphoenolpyruvate carboxylase, purified from maize leaves, is rapidly inactivated by the fluorescence probe dansyl chloride. The loss of activity can be ascribed to the covalent modification of an R-NH2 group, presumably the e-NH2 group of lysine. Analysis of the data by the statistical method of Tsou [Sci. Sin. ZI, 153.5-1.558 (1962)l provides clear evidence that at pH 8 eight R-NH2 groups can be modified in the tetrameric form of the enzyme, four of which are essential for catalytic activity. Essential gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 35 publications
0
10
1
1
Order By: Relevance
“…tions suggest that two lysines per subunit are accessible for chemical modifications and one of these is essential for the catalytic activity [15][16][17]. We previously reported that one of the conserved lysines, Lys 6°° in F trinervia, is likely to be linked to bicarbonate binding [20], a finding at variance with chemical modification studies [19].…”
Section: Gly 829 Mutationcontrasting
confidence: 43%
See 2 more Smart Citations
“…tions suggest that two lysines per subunit are accessible for chemical modifications and one of these is essential for the catalytic activity [15][16][17]. We previously reported that one of the conserved lysines, Lys 6°° in F trinervia, is likely to be linked to bicarbonate binding [20], a finding at variance with chemical modification studies [19].…”
Section: Gly 829 Mutationcontrasting
confidence: 43%
“…However, it is possible that the loss of activity may by the result of several residues being simultaneously modified by pyridoxal 5'-phosphate [19]. Furthermore, the reagents used to modify lysine residue of PEPC, i.e., pyridoxal 5'-phosphate [15], eosin isothiocyanate [16] and dansyl chloride [17], are large cyclic molecules which could sterically impede the entry of substrate to the active site. In contrast, substitution of lysine by threonine or glycine is non-obstructive and allows the roles of the residues to be assessed directly.…”
Section: Gly 829 Mutationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical modifications of amino acid residues have shown that some histidine, lysine and arginine residues are essential for the catalytic activity of PEPC [6][7][8][9][10]. Although their precise locations can not be determined by this approach, the conserved residues are likely to be associated with substrate-binding sites and they have served as a guide for site-directed mutagenesis to identify the residues involved.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the molecular structure of the C4 plant enzyme, only recently some reports have presented evidence on the possible spatial arrangement of the carboxylase molecule (1,25,27). Further evidence comes from the dissociation observed after chemical modification of histidine or thiol groups (28) or after exposure to increasing ionic strength (26).…”
mentioning
confidence: 99%